The effect on the birth experience of women and partners of giving birth in a "birth environment room": A secondary analysis of a randomised controlled trial. (September 2022) - Hansen, Merete Lausten; Lorentzen, Iben Prentow; Andersen, Charlotte S.; Jensen, Henriette Svenstrup; Fogsgaard, Ann; Foureur, Maralyn; Jepsen, Ingrid; Nohr, Ellen Aagaard
Abstract: Objective: To evaluate women and partners' experience of birth in a "birth environment room" compared to a standard birth room. Design: A single centre parallel randomised controlled trial. Women and partners were enrolled during a 3-year period (May 2015 to March 2018). Setting: The Department of Obstetrics and Gynaecology at Herning Hospital, Denmark. Participants and intervention: A total of 680 Danish speaking nulliparous women, more than 18 years old, with a singleton pregnancy in cephalic presentation, and a spontaneous onset of labour, and their partners were randomly assigned to give birth in a "birth environment room" ( n  = 340) or in a standard birth room ( n  = 340) on arrival at the birth unit. Measurements and findings: Outcomes were the overall birth experience and overall satisfaction with care, measured on a Likert scale, obtained in the postpartum questionnaire sent to the women 6 weeks after birth and to their partners 1/2 weeks after birth. Other outcomes were "staff support for partner", "undisturbed contact with new-born", "feeling of being listened to", "level of information", "attention to psychological needs", "suggestions for pain-relief", "participation in decision-making", "midwife present when wanted", "support from midwife", "birth wishes were met", "loss of internal control" (only women), "loss of external control", "support from partner" (partners: "being supportive for partner"), "importance of physical environment for birth" and "importance of physical environment for staff´s ability to involve the women" (only women). All outcomes were prespecified. We applied Mann Whitney U test for comparing the two groups. Data were collected from 326 women and 236 partners in the intervention group and from 315 women and 209 partners in the control group. The intention-to-treat analysis revealed no difference in the overall experience of birth for women or partners (p 0.81 and p 0.17, respectively). Partners in the intervention group reported more overall satisfaction with care compared to partners in the control group (p 0.048). In the intervention group, fewer women and partners responded they had not had the opportunity for undisturbed contact with their new-born in the first hours after birth (RR 0.19 (95% CI 0.04-0.87) and OR 0.00 CI (0.00–0.83), respectively). Otherwise, there were no differences between groups. The thematic analysis revealed that many women and partners felt they were not able to benefit from the features in "the birth environment room" in the most intense hours of birth. Key conclusion and implications for practice: "The birth environment room" did not improve the overall experience of birth for women and partners. Partners in the intervention group were overall more satisfied with care. These findings are of importance in the developing of physical birth environments that support the mental/emotional process of labour.